2017
DOI: 10.3171/2016.6.jns16653
|View full text |Cite
|
Sign up to set email alerts
|

Topographic changes in cerebral blood flow and reduced white matter integrity in the first 2 weeks following revascularization surgery in adult moyamoya disease

Abstract: OBJECTIVE After revascularization surgery, hyperperfusion and ischemia are associated with morbidity and mortality in adult moyamoya disease (MMD). However, structural changes within the brain following revascularization surgery, especially in the early postsurgical period, have not been thoroughly studied. Such knowledge may enable improved monitoring and clinical management of hyperperfusion and ischemia in MMD. Thus, the objective of this study was to investigate the topographic and temporal profiles of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Moreover, the area of increased regional CBF shifted to the lateral prefrontal cortex approximately one week after the surgery. 25 This phenomenon matches with the ICH pattern in this study because of the onset timing and hematoma location at an earlier phase, such as POD 0-2; and the typical TNDs due to CHP occurring around POD 7-8. Importantly, the present study shows that some of the cases developed ICH before the standard postoperative CBF assessment or exhibited ICH despite reduced increase in CBF after surgery.…”
Section: Involvement Of Cerebral Blood Flowsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the area of increased regional CBF shifted to the lateral prefrontal cortex approximately one week after the surgery. 25 This phenomenon matches with the ICH pattern in this study because of the onset timing and hematoma location at an earlier phase, such as POD 0-2; and the typical TNDs due to CHP occurring around POD 7-8. Importantly, the present study shows that some of the cases developed ICH before the standard postoperative CBF assessment or exhibited ICH despite reduced increase in CBF after surgery.…”
Section: Involvement Of Cerebral Blood Flowsupporting
confidence: 87%
“…3,23,24 The discrepancy between typical CHP and ICH, as observed in this study, with respect to onset timing and location, can be explained by the findings of a past study that reported a topographic change in regional CBF in the first 2 weeks after surgery. 25 This report demonstrated that direct Tokairin 11 revascularization provides additional CBF to the basal ganglia and subcortical lesions in the frontotemporal lobes immediately after surgery. Moreover, the area of increased regional CBF shifted to the lateral prefrontal cortex approximately one week after the surgery.…”
Section: Involvement Of Cerebral Blood Flowmentioning
confidence: 69%
“…In particular, it has not been determined whether the temporal correlations of low-frequency BOLD signals are altered in patients with an otherwise apparently healthy brain, who are potential candidates requiring early detection of cognitive impairments. Previous investigations using voxel-based analysis have demonstrated altered distribution of regional cerebral blood flow (rCBF) in MMD, before and after the revascularization surgery [ 21 , 22 ]. However, the extent of alterations in low-frequency BOLD signals associated with vascular lesions and rCBF has not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, measurements of the brain microstructure can be used to evaluate the effects of therapeutic interventions such as revascularization surgery. [7][8][9] Diffusion imaging, postacquisition image processing techniques, and quantification of diffusion parameters allow one to determine the profile of white matter injuries such as reduced fiber density, demyelination, and axonal injury. 10 In moyamoya disease, DTI parameters such as fractional anisotropy (FA), radial diffusivity, and mean diffusivity are altered.…”
mentioning
confidence: 99%